Utilization of Canva Application as Making Thematic Learning Videos - Fiidznillah, Rizki; Cholila, Zahiratu; Nurlatipah, Nurlatipah (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. This discussion is about the use of canva software as a thematic learning video for Class V Semester I Theme two Subtheme 1 Learning three at State Elementary School 05 IX Koto, Dharmasraya Regency Purpose. Is the purpose of this study, namely to explore how the utilization of canva software in making learning videos for teachers and the impact of thematic learning videos on Class V Semester 1 Theme 2 Subtheme 1 Learning 3 students at State Elementary School 05 IX Koto. Method. The research uses participatory observation techniques and in-depth interviews that are spiked using data collection using describing the features of the canva software Results. that the utilization of the canva application as a thematic learning video for Class V Semester 1 Theme 2 Subtheme 1 Learning 3 at negri 05 IX Koto basement school, Dharmasraya Regency, can be said to be successful. Conclusion. Based on the results of the research that has been done, it can be concluded that the canva application-based learning video is very feasible to use in learning. The use of learning videos is very interesting for students so that students are motivated to carry out learning. In the covid-19 pandemic, online learning emphasizes the development of online-based learning media such as the use of the canva application in making learning media in the form of learning videos can provide new meaning and color for students in the learning process in thematic learning Class V Semester 1 Theme 2 Subtheme 1 Learning 3 at negri 05 IX Koto basic shool, Dharmasraya Regency which is effective, creative and innovative.